Baltic and Polish Politicians in Exile and Their Vision of Post-War Peace Agreements in Eastern Europe, 1940–1945 - Ilmjärv, Magnus (Genocidas ir rezistencija, 2024)
The article examines two key topics: what vision the leading Baltic politicians in exile had of the post-war world order, and what vision Polish politicians in exile had of the post-war world order, specifically in terms of Lithuania, Latvia, Estonia and East Prussia. The main focus is on the Memel/Klaipėda question. The Vilnius question is also addressed to the extent that it is related to the Memel/Klaipėda question. This question is important for understanding the relations between Baltic and Polish émigré politicians during World War II. The article’s limited scope did not leave space for negotiations between the Soviet government and the Polish government-in-exile or between the Soviet government and the Lithuanian and Polish communists on the issue of East Prussia and Klaipėda. The article tries to avoid fundamental generalizations, and does not attempt to provide conclusive answers to many of the questions and problems that have arisen.
Keywords: International relations; the Baltic question; the Memel/Klaipėda question; East Prussia; World War II; relations between Baltic and Polish exiles; visions of the post-war world order